The study of dynamics and strength of hydraulic crane-manipulating installations on a movable chassis - Lagerev A.V.; Lagerev I.A.; Milto A.A. (Научно-технический вестник Брянского государственного университета)
The modified version of previously reviewed technique for dynamics and stress analysis of fixed-base manipulators (articulating cranes) is suggested. The idea is to insert a fictitious six-degrees-of-freedom joint between a fixed support and manipulator’s base thus eliminating fixed base motion constraints. The technique has been implemented in the software package KBCrane and used for dynamics and stress analysis of an articulating crane mounted on a ship rocking in waves. Based on the results of simulation the distribution and level of stress in the crane is estimated.